Comparative Analysis of Sensor Activity of Carbon Nanotubes Modified with Functional Groups - N.P. Boroznina; I.V. Zaporotskova; S.V. Boroznin (Журнал нано- та електронної фізики)
This article presents theoretical study of sensor activity of nanosystems based on a carbon nanotube modified with functional group (carboxyl, aminogen, nitrogroup) on some metal atoms and ions. Calculations were performed within the frameworks of molecular cluster model with application of semiempirical MNDO method and density functional theory DFT. The mechanism of binding functional groups to the open border of single-walled zig-zag carbon nanotubes for the purpose of formation of a chemically-active sensor based on them has been investigated. Main geometric and electron energy characteristics of built systems have been defined. Interaction of the sensors built in this fashion with atoms and ions of some metals: potassium, sodium, lithium has been investigated.